Transhepatic device closure of atrial septal defect in children associated with interrupted inferior vena cava - Bhargavi Dhulipudi; Shweta Bakhru; Jagadeesh R Singh; Nageswara Rao Koneti (Annals of Pediatric Cardiology, 2022)
Percutaneous transcatheter closure of fossa ovalis atrial septal defect (FOASD) is an established procedure. When femoral venous approach is unfeasible due to interrupted inferior vena cava (IVC) or occluded femoral veins, other interventional methods through transjugular, transhepatic approach, or surgical closure can be performed. We report two cases of transhepatic device closure of FOASD associated with IVC interruption successfully performed without any complications.